2015
DOI: 10.1080/10942912.2015.1013632
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Protein Hydrolysates and Color During Fermentation ofMucor-TypeDouchi

Abstract: The correlations between the color of douchi and different protein hydrolysates from the post-fermentation period were analyzed. The results showed that peptides had the highest correlation with the color change, while free amino acids were second, which indicated that peptides and free amino acids were more involved in the Maillard reaction. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed that the 7S component may be more involved in the Maillard reaction during the pre-fermentation of douc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Hydrolysates of protein and sugar hydrolyzed from carbohydrates are important sources for Millard Reaction (MR) which occurs between reducing sugars and amino compounds (Langer and Rzeski, 2014;Wang et al, 2013). Therefore, as described by Zhang et al (2015), the degree of protein hydrolysis during fermentation might be associated with the significant color change of the fermented TVP products in our experiment. TVP extruded at lower MC (40%) exhibited significantly higher total color change (DE) and redness (a) than those of TVP extruded at higher MC (50%) during fermentation.…”
Section: Colormentioning
confidence: 80%
“…Hydrolysates of protein and sugar hydrolyzed from carbohydrates are important sources for Millard Reaction (MR) which occurs between reducing sugars and amino compounds (Langer and Rzeski, 2014;Wang et al, 2013). Therefore, as described by Zhang et al (2015), the degree of protein hydrolysis during fermentation might be associated with the significant color change of the fermented TVP products in our experiment. TVP extruded at lower MC (40%) exhibited significantly higher total color change (DE) and redness (a) than those of TVP extruded at higher MC (50%) during fermentation.…”
Section: Colormentioning
confidence: 80%
“…Mucor ‐ type Douchi was prepared according to the process (Zhang et al ., ) with slight modifications. The processes were as follows: first step was soya bean steaming, in which soya bean was washed, soaked, drained and then steamed at 100 °C for 120 min; second step was prefermentation process in which the streamed soya bean was cooled to below 40 °C, inoculated with the A .…”
Section: Methodsmentioning
confidence: 99%
“…() investigated the effect of fermented rice culture on the quality of low‐salt Aspergillus ‐ type Douchi , and the results showed that it could promote a rapid growth of yeasts and lactic acid bacteria and improved sensory characteristics when supplemented with 10% and 15% fermented rice culture. Characteristic colour of Mucor ‐ type Douchi also depended on the parameters of postfermentation, such as peptides and free amino acids, which may be involved in the Maillard reaction (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Proteins were broken down into polypeptides and amino acids by microbial enzymes during Douchi fermentation. [24,25] Our previous study results shows that the peptide content of Douchi fermented with Mucor wutungkiao had been increasing during the fermentation [26] . Consequently, we can concluded that Douchi ripening accompanied with nutrient decomposition under the action of microbial enzyme, and the increase of peptide and amino acid content contributed to protein digestibility [27] .…”
Section: Changes Of Crude Protein Content During Douchi Fermentationmentioning
confidence: 97%